Analysis of Routing Protocols for Large Scale Multihop Multirate MANETs (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper, we perform rigorous analysis of MANET routing protocols selected from different categories over various scenarios using a large set of performance evaluation metrics. The traffic that we model on source-destination pairs is the video streams that consist of varying sized data frames and the inter-packet time is very low. In this way, we can check the MANET routing protocols over varying data sets and can provide the analysis that among the existing MANET routing protocols which routing protocol is best suited for data transmission over MANETs. To analyze the behavior of various routing protocols during the data communication in MANETs, we generate simulation results over various MANET scenarios consists of varying number of nodes and source destination pairs. The simulation process is done by using the open source simulator NS-3. We generate and analyze the scenarios where the effects of data communication is evaluated and analyzed over the increase in network mobility and network data traffic. The work is helpful for the students working on the various issues on MANETs as attacks, Quality-of-Service etc to identify which protocol they should use for their work as a base routing protocol. Â